2006
DOI: 10.1088/0957-4484/17/10/014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on sessile droplet contact angle

Abstract: This paper investigates the change in contact angle of droplets of fluid containing dispersed nanoparticles (nanofluid) functionalized with thioglycolic acid molecules as a function of the concentration and size of nanoparticles, and the quality and composition of the substrate material. Bismuth telluride nanoparticles with an average size ranging from 2.5 to 10.4 nm and functionalized with thioglycolic acid groups were grown by a microemulsion method and dispersed in water. Experimental measurements of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
144
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 25 publications
11
144
0
Order By: Relevance
“…However, there is a long ongoing debate on whether or not nanoparticles (NPs) adsorbed at an interface can reduce the interfacial tension. [1][2][3][4][5][6][7][8][9][10][11] Briefly,…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a long ongoing debate on whether or not nanoparticles (NPs) adsorbed at an interface can reduce the interfacial tension. [1][2][3][4][5][6][7][8][9][10][11] Briefly,…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the nanolubricant with better dispersibility, stronger wettability and higher concentration is more inclined to decrease rolling force to a larger extent. Many researchers have reported that the wettability of nanolubricant improves with increasing the concentration of NPs into base liquid [26][27][28]. Therefore, when the concentration of nano-TiO 2 is lower than 4.0 wt%, there are insufficient TiO 2 NPs left to form lubricating film and make rolling effect due to loss of nanolubricants when contacting the hot steel surface.…”
Section: Fib-tem Analysismentioning
confidence: 99%
“…One step: substrate was coated and dried, using 500 rpm for 250 sec.) Surface wettability has an important role on thickness of nanofluid on substrate [9][10][11][12][13][14][15][16]. The thickness of nanofluid decreases, as affinity of liquid for substrate increases.…”
Section: Deposited Porous Layer Of Tio 2 Nanoparticlesmentioning
confidence: 99%